True Random Number Generator Based on RRAM-Bias Current Starved Ring Oscillator - D. Arumi; S. Manich; A. Gomez-Pau; R. Rodriguez-Montanes; M. B. Gonzalez; F. Campabadal (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits, 2023)
This work presents a resistive random access memory (RRAM)-bias current-starved ring oscillator (CSRO) as true random number generator (TRNG), where the cycle-to-cycle variability of an RRAM device is exploited as source of randomness. A simple voltage divider composed of this RRAM and a resistor is considered to bias the gate terminal of the extra transistor of every current starved (CS) inverter of the ring oscillator (RO). In this way, the delay of the inverters is modified, deriving an unpredictable oscillation frequency every time the RRAM switches to the high resistance state (HRS). The oscillation frequency is finally leveraged to extract the sequence of random bits. The design is simple and adds low area overhead. Experimental measurements are performed to analyze the cycle-to-cycle variability in the HRS. The very same measurements are subsequently used to validate the TRNG by means of electrical simulations. The obtained results passed all the National Institute of Standards and Technology randomness tests (NIST) tests without the need for postprocessing.